Mapping the Barriers of Big Data Process in Construction: The Perspective of Construction Professionals - Bernard Tuffour Atuahene; Sittimont Kanjanabootra; Thayaparan Gajendran (Buildings, 2023)
This study identifies, maps and thematizes the barriers to the big data process in the construction industry from the perspective of construction professionals. Australian construction professionals with varying experiences in the big data process were interviewed. Qualitative data analysis identified forty barriers in the big data process and five themes: people, knowledge, technology, data, and environment. The barriers were further mapped, with some transcending more than one stage in the big data process. Many of the barriers have not been empirically identified in previous studies. By implication, mapping the barriers across the big data process enables professionals/construction firms to visualize the potential lapses before and/or during implementation. Therefore, the study offers professionals/construction firms strategic insights and operational perspectives for planning and deploying big data processes.